ANALISIS KETERAMPILAN DASAR PERMAINAN SEPAK BOLA PADA EKSTRAKURUKULER MTS NW LINGSAR TAHUN 2019 - Julhizam, Julhizam; Syah, Herman; Akhmad, Noor (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research is motivated by the lack of basic skills in the basic game of football in MTs NW Lingsar extracurricular. This research was conducted with the aim to find out the basic skills of playing soccer. The design of this study included descriptive research with a quantitative approach. The method used is a survey with data collection techniques using tests and measurements. The study population was all extracurricular MTs NW Lingsar with 20 research subjects or using population study techniques. The data analysis technique used is descriptive statistical data analysis technique, which is the technique of grouping the results of the t score into five categories of football test norms, then the data that has been grouped in the category of basic soccer skill criteria is calculated using the percentage of basic soccer skills using the percentage formula P = F / N x 100%. And it can be concluded that the basic ability of soccer in MTs NW Lingsar extracurricular is in the sufficient category with a percentage of 50%.